Rhomboid flap: An option to medial canthal reconstruction - Rafael Corredor-Osorio (Our Dermatology Online, 2017)
Medial canthal defects after wide local excision of basal cell carcinoma can range from small to medium size which can be reconstructed by using full thickness skin-grafts or defect local flaps. This report describes the case of 51-year-old woman with a medial canthal tumor. The large defect after of excision was successfully reconstructed with local rhomboid flap. The result cosmetic was highly satisfactory. Local rhomboid flap reconstruction is a safe, rapid and practical technique for skin defects in the canthal medial region after tumor excisions.